PERSEPSI MAHASISWA STKIP WIDYA YUWANA MADIUN TENTANG HUBUNGAN ANTARA PEMBINAAN SPIRITUALITAS DAN PEMBINAAN KARYA PASTORAL - Yuventius Fusi Nusantoro; Antonia Bamban Puspitasari (Bahasa Indonesia, 2018)
As an institute that prepares a catechist aspirant, STKIP Widya Yuwana Madiun operated spirituality guidance and pastoral activity training and guidance. Because, spiritual's life and apolostate activity mutually support each other. But, guidance and training was held not necessarily got fully attentions. Based of the case, researcher intend obtain a deep understanding of student comprehention about spirituality and pastoral activity guidance in STKIP Widya Yuwana Madiun, and student perception about both connection. The research result indicate that STKIP Widya Yuwana Madiun's student observe a connection between spirituality guidance and pastoral activity guidance as an unity that mutually support each other. Student meaningful the spirituality and pastoral activity guidance based by it's purpose, that is by personal preparation, developing of relations with God and fellow, spirituality of attendance, and reaction concerning life vacation as a catechist aspirant.